How to measure "green" economy: methodological approaches (Eurasian Journal of Ecology, 2016)
Known methods of an economic assessment of natural resources, ecosystem services, ecological extremeness in a context of the principles of "green" economy are considered. Aspects of criticism of gross domesticproduct as inefficient indicator reflecting ekologo-economic factors, level of insufficient financing and subsidizing of "green" sectors are analyzed. Calculations of an assessment of natural resources (mineral rawmaterials, land, water resources) Kazakhstan are given.
Keywords: "green" economy; economic assessment; gross domestic product; natural resources; ecology